National movement in a princely state - Misra, S. C., 1939- (Jaipur, India : Pointer Publishers, 1993)
Study with reference to Bharatpur (Princely State), Rajasthan.
Includes bibliographical references and index.
Keywords: Nationalism -- India -- Bharatpur (Princely State) -- History; Bharatpur District (India) -- Politics and government